Exploring the Role of Social Media in Promoting Collaborative Learning: A Systematic Review - Sahoo, Parshuram; Pradhan, Jyoti Sankar (RADINKA JAYA UTAMA PUBLISHER, 2025)
This systematic literature review examines the power of social media on facilitating collaborative learning across various educational environments. PRISMA strategy was adopted to conduct this review. Data were collected by searching Google Scholar, Scopus and ERIC database. By applying inclusion and exclusion criteria 28 articles were selected. Based on the thorough analysis of data from 28 studies, this study seeks to understand how platforms like Facebook, WhatsApp, Twitter, and others affect peer interaction, knowledge sharing, and learner engagement. This paper looks at the benefits and drawbacks of using social media for collaborative learning. It highlights how social media can foster informal learning environments while also acknowledging the potential for diversions and off-topic conversations. The main conclusions indicated that organised activities, direct involvement of instructors, and careful selection of platforms are essential for optimising the educational benefits of social media. To maximize social media's effectiveness in promoting collaborative learning, guidelines are provided to educators. This analysis suggests that social media can be used strategically to enhance learning and prepare kids for a future in which they will be connected to the internet.